Rights & Wrongs: Human Rights Television: War Crimes Tribunal
Episode no. 201 of the “Rights & Wrongs” series with Charlayne Hunter-Gault. The program investigates: the role of the ICTY in bringing to justice and prosecute the people responsible for the crimes committed during the wars in the former Yugoslavia; the economic relationship between U.S. and China in light of the human rights violations in China; the ongoing war in Angola; the motion picture “In the Name of the Father.” The program features: Cherif Bassiouni (UN Commission of Experts), Kenneth Roth (Human Rights Watch), Henry Kissinger (Former Secretary of State), Sidney R. Jones (Human Rights Watch, Asia), John Ackerly (International Campaign for Tibet), Marc Gagnon (Field Director, C.A.R.E), and Jim Sheridon (Film Director).